Formulation and Characterization of Solid Lipid Nanoparticles Loading RF22-c, a Potent and Selective 5-LO Inhibitor, in a Monocrotaline-Induced Model of Pulmonary Hypertension - Liparulo, Angela; Esposito, Renata; Santonocito, Debora; Muñoz-Ramírez, Alejandra; Spaziano, Giuseppe; Bruno, Ferdinando; Xiao, Jianbo; Puglia, Carmelo; Filosa, Rosanna; Berrino, Liberato; D'Agostino, Bruno (Frontiers in Pharmacology, 2020)
Pulmonary arterial hypertension (PAH) is a rare but fatal disease characterized by persistent elevated blood pressure in the pulmonary circulation, due to increased resistance to blood flow, through the lungs. Advances in the understanding of the pathobiology of PAH clarify the role of leukotrienes (LTs) that appear to be an exciting new target for disease intervention. Over the years, our group has long investigated this field, detecting the 1,2-benzoquinone RF-22c as the most powerful and selective competitive inhibitor of the enzyme 5-lipoxygenase (5-LO). With the aim to improve the bioavailability of RF-22c and to confirm the role of 5-LO as therapeutic strategy for PAH treatment, we developed a solid lipid nanoparticle (SLN) loaded with drug. Therefore, in monocrotaline (MCT) rat model of PAH, the role of 5-LO has been investigated through the formulation of RF-22c-SLN. The rats were randomly grouped into control group, MCT group, and MCT + RF22-c group. After 21 days, all the animals were sacrificed to perform functional and histological evaluations. RF22-c-SLN treatment was able to significantly reduce the mean pulmonary arterial pressure (mPAP) and precapillary resistance (R-pre) compared to the MCT group. The MCT induced rise in medial wall thickness of pulmonary arterioles, and the cardiomyocytes width were significantly attenuated by RF22-c-SLN formulation upon treatment. The results showed that the selective inhibition of 5-LO improved hemodynamic parameters as well as vascular and cardiac remodeling by preventing induced pulmonary hypertension. The improved sustained release properties and targeting abilities achieved with the innovative nanotechnological approach may be therapeutically beneficial for PAH patients as a consequence of the increase of pharmacological effects and of the possible reduction and/or optimization of the drug frequency of administration.